Determinants of orphan drug health technology assessment in South Korea: an empirical analysis - Lee, Se Hee; Lee, Sung Kyung; Lee, Jong Hyuk; Bang, Joon Seok (Frontiers in Pharmacology, 2025)
BackgroundOrphan drug pricing in South Korea, including its workings and determinants, is a complicated aspect of the country’s healthcare system. Therefore, this study identified the factors associated with the pricing of orphan drugs in South Korea.MethodsThe study screened 66 orphan drugs out of the whole set of newly reimbursed drugs from 2012 to 2022. The analysis presented the characteristics of the orphan drugs and accounted for correlations between treatment cost and other seemingly related variables. Formal multivariate regression analysis indicated associated factors in multivariate settings.ResultsAnnual treatment cost per patient displayed a weakly negative correlation with the number of patients. Meanwhile, treatment cost exhibited a strongly positive correlation with the average of adjusted prices in seven advanced countries, reaching an adjusted R-squared value of 0.99. Treatment cost also showed a positive correlation with budget impact.ConclusionThe pricing of orphan drugs in South Korea is predominantly influenced by external reference pricing. Drugs targeting smaller patient populations tend to be priced higher. This finding can guide policymakers, pharmaceutical companies, and healthcare providers in their efforts to balance patient accessibility with the sustainable development of orphan drugs and the financial sustainability of public health insurance.